Plants’ bioactive secondary metabolites in the management of sepsis: Recent findings on their mechanism of action - Mahomoodally, Mohamad Fawzi; Aumeeruddy, Muhammad Zakariyyah; Legoabe, Lesetja Jan; Dall’Acqua, Stefano; Zengin, Gokhan (Frontiers in Pharmacology, 2022)
Sepsis is a severe inflammatory response to systemic infection and is a threatening cause of death in intensive care units. In recent years, a number of studies have been conducted on the protective effect of natural products against sepsis-induced organ injury. However, a comprehensive review of these studies indicating the mechanisms of action of the bioactive compounds is still lacking. In this context, this review aimed to provide an updated analysis of the mechanism of action of plants’ secondary metabolites in the management of sepsis. Scopus, Science Direct, Google Scholar, and PubMed were searched from inception to July 2022. A variety of secondary metabolites were found to be effective in sepsis management including allicin, aloin, cepharanthine, chrysin, curcumin, cyanidin, gallic acid, gingerol, ginsenoside, glycyrrhizin, hesperidin, kaempferol, narciclasine, naringenin, naringin, piperine, quercetin, resveratrol, rosmarinic acid, shogaol, silymarin, sulforaphane, thymoquinone, and zingerone. The protective effects exerted by these compounds can be ascribed to their antioxidant properties as well as induction of endogenous antioxidant mechanisms, and also via the down-regulation of inflammatory response and reduction of biochemical and inflammatory markers of sepsis. These findings suggest that these secondary metabolites could be of potential therapeutic value in the management of sepsis, but human studies must be performed to provide strength to their potential clinical relevance in sepsis-related morbidity and mortality reduction.